Vaccination to modulate atherosclerosis. (May 2015) - Kimura, Takayuki; Tse, Kevin; Sette, Alessandro; Ley, Klaus
Abstract Atherosclerosis is a chronic inflammatory disease of the artery wall. Adaptive immunity plays a key role in the pathogenesis of atherosclerosis. Recently, modulation of the immune response against atherosclerotic plaque antigen(s) has attracted attention as a potentially preventive and therapeutic approach. Here, we review a series of studies on immunization with various antigens targeting treatment and prevention of atherosclerosis. Atherosclerosis-related antigens include oxidized low-density lipoprotein (LDL), apolipoprotein B-100 (ApoB-100) and heat shock protein (HSP) 60/65. Accumulating evidence supports the idea that immunization with these antigenic proteins or peptides may reduce atherosclerosis. In this review, we discuss the current status of immunization studies and possible associated mechanisms of atheroprotection.